Sistem penyelarasan belanjawan projek pembangunan perisian - Ibrahim, Siti Nurkhadijah Aishah (2006)
Recently, there are various software utilize to estimate software development project. Conventionally, most organization that involved in develop software development project used the software to ease the estimation problems. However, project manager lately has figured out difficult to find the convenient software for their needs because of highest quantity estimation software project in the market. In order to achieve local economic market in budgeting, this project has come out with new System Estimation of Software Development Project using Early Design Model in Constructive Cost Model (COCOMO) 2.0. So, due to this software development prototype model has been applied as it can be rapidly developed. At the end, each type of model, technique and method involved in the development software hopefully will convenient for estimate measurement in latest software development project. In fact, it is easier for project manager to do early estimation for the upcoming software development project.